The gender-specific reactions of student’s central nervous - Bosenko, A.; Orlyk, N.; Topchii, M.; Mykhaliuk, Ye. L.; Horokhovskyi, Ye.; Михалюк, Євген Леонідович (My University, 2023)
Purpose: to study the response of the central nervous system and the characteristics of neurophysiological processes in students of both genders during physical load. Material & Methods: in the study participated 58 female and 82 male students. All participants were classified as individuals with high level of physical activity according to survey data. The general health of students and their demand to participate in this study were determined by interview and examination. The reaction of the central nervous system was studied using a reflexometer according to the method proposed by T. Loskutova. The method is based on the analysis of the statistical distribution of multiple measurements of the simple visual-motor reaction time and represents a quantitative characteristic of the functional state of the central nervous system. Reflexometry was carried out at a relative resting state and at the 5th minute of recovery period after a physical load in the bicycle test, carried out according to the method proposed by D. Davidenko et al. The analysis of the obtained data was performed using Microsoft Excel 2016 and SPSS 20.0 statistical package. системи та особливості протікання нейрофізіологічних процесів у студентів обох статей під час м’язової діяльності. Матеріали і методи: обстежені студенти 1–2 років навчання з високою руховою активністю (58 дівчат і 82 юнака) з дотриманням всіх правил біоетики. Використовували методику оцінки функціонального стану головного мозку за даними зорово-рухової реакції. Рефлексометрія проводилась в стані відносного м’язового спокою і на п’ятій хвилині відновлення після фізичного велоергометричного навантаження, яке проводилося за методикою Д. Давиденка і співавторів. Аналіз отриманих даних проводився за допомогою статистичних пакетів Microsoft Excel 2016 та SPSS 20.0.
Гендерні особливості реакції центральної нервової системи студентів на фізичні навантаження
Mykhaliuk Ye. L. - orcid.org/0000-0003-3607-7619
Keywords: central nervous system; functional state of the brain; reaction stability; level of functional capabilities; functional level of the system; reflexometry; students; центральна нервова система; функціональний стан головного мозку; стійкість реакції; рівень функціональних можливостей; функціональний рівень системи; рефлексометрія; студенти